Let f ( x ) be a linear function. Given f ( 6 ) − f ( 2 ) = 1 2 find the value of f ( 1 2 ) − f ( 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Strictly speaking a linear function is f ( x ) = c . x + a so you can't assume that f ( n x ) = n . f ( x ) but when you do the calculations the a cancels out - so the result is the same.
Log in to reply
a linear function is a function that obeys the two properties f(kx) = kf(x) and f(x + y) = f(x) + f(y)
Well, linear functions are real functions which map x to ax+C for some real a and C
Assume the real function in this problem is f(x) = ax+C
We're given that f(6)-f(2)=12
This implies that f(6)-f(2)= 6a + C - (2a+C) = 4a = 12
Solving, we get a = 3
Now, look into the other part
f(12)-f(2)=12a+C -(2a+C) = 10a
Substitute, a with 3 and get the answer as 30
I have a question... I got the answer by using f as an unknown variable. I just looked for the value of f and once I found it, I substituted it. Is it wrong to do this?
Log in to reply
In this case it doesn't affect the result - but in general f(x) isn't the same as f*x. Even as a linear function f ( x ) = m . x + c and for non-linear functions the definitions could be much more complex.
Since f ( x ) is a linear function, then we can compute for its slope x 1 − x 2 f ( x 1 ) − f ( x 2 ) = m .
Recomputing, we can have f ( x 1 ) − f ( x 2 ) = m ( x 1 − x 2 ) .
With this, we now have the following:
f ( 6 ) − f ( 2 ) = 1 2 = m ( 6 − 2 ) which produces m = 3 .
Thus, f ( 1 2 ) − f ( 2 ) = m ( 1 2 − 2 ) = 3 ( 1 0 ) = 3 0
Nice method
Very methodical!
• Definition of a linear function: f is called linear if it satisfies (i) f(cx) = cf(x) and (ii) f(x + y) = f(x) + f(y) for any vectors x, y and any scalar constant c.
So,
12 = f(6) - f(2) = f(6) + f(-2) = f(6 - 2) = f(4).
Now,
f(12) - f(2) = f(3 * 4) - f((1/2) * 4) = 3f(4) - (1/2)f(4) = 3 * 12 - (1/2) * 12 = 30.
A linear function is always f ( x ) = m . x + c i.e. always a straight line when graphed. so you can't assume that either of your two identities hold true - they only do when c is zero. In this special case though - when you are talking about the difference between functions - the c values cancel out.
Let 6x-2x=12 OR 4x=12...thus x=3.
Now,
to find 12x-2x = 12(3)-2(3) = 36-6 = 30
Let the function
f
(
x
)
be represented as
A
x
+
B
=
0
, as it is the general form of linear algebraic functions.
So,
f
(
6
)
=
6
A
+
B
f
(
2
)
=
2
A
+
B
f
(
6
)
−
f
(
2
)
=
(
6
A
+
B
)
−
(
2
A
+
B
)
1
2
=
6
A
+
B
−
2
A
−
B
1
2
=
4
A
A
=
3
So,
f
(
1
2
)
−
f
(
2
)
=
(
1
2
A
+
B
)
−
(
2
A
+
B
)
⇒
f
(
1
2
)
−
f
(
2
)
=
1
0
A
⇒
f
(
1
2
)
−
f
(
2
)
=
3
0
Linear function means st. line. Given change in y = 12 change in .x = 6 - 2 = 4.
Slope = 12/4 = 3. Change in x now is 12 - 2 = 10...
.Hence change in y = 3 * 10 = 30.
f ( 6 ) − f ( 2 ) = 1 2 ... or,difference of every f(1)= 4 1 2 = 3
so, f ( 1 2 ) − f ( 2 ) = f ( 3 × 1 2 ) − f ( 3 × 2 ) = 3 6 − 6 = 3 0
f(x) is lineal so, when it goes from (2) to (6) takes 4 horizontal steps, and when goes from (2) to (12) takes 10. Then in order to get the second amount of vertical steps we must multiply the first amount, 12, by 10/4 = 2.5, then 24 + 6 = 30.
Write f(x) = ax + b since it is a linear equation,
f(6) - f(2) = 12 is equal to write
6a + b - 2a - b = 12 or
4a = 12
a = 3
so the function is f(x) = 3x + b .
Than f(12) - f(2) = 36 + b - 6 - b = 30
The definition of a slope is m = (y - y1) / (x - x1) or, ((f(x) - f(x1)) / (x - x1))
We can see what the x values are; for f(6) the x-value is 6, and for f(2) the x-value is 2.
Therefore: ((f(6) - f(2)) / (6 - 2)) = m. Given is that f(6) - f(2) = 12. The slope, m, is thus 12 / 4 = 3.
Since it is give that we are dealing with a linear function, we therefore know that ((f(12) - f(2)) / (12 - 2)) = 3, and so (f(12) - f(2)) = 10 * 3 = 30.
given ,f(x) is a linear function.then let it be ax+b. then,f(6)=6x+b,f(2)=2x+b. then f(6)-f(2)=(6x+b)-(2x+b) => 6x+b-2x-b=12 => 4x=12 => x=3 for f(12)-f(2)=12x+b-2x-b=12(3)-2(3)=36-6=30
Problem Loading...
Note Loading...
Set Loading...
Since it is linear function, f ( x ) satisfies f ( c x ) = c f ( x ) . Then,
1 2 f ( 2 ) = f ( 6 ) − f ( 2 ) = f ( 3 ( 2 ) ) − f ( 2 ) = 3 f ( 2 ) − f ( 2 ) = 2 f ( 2 ) = 6
Therefore,
f ( 1 2 ) − f ( 2 ) = 6 f ( 2 ) − f ( 2 ) = 5 f ( 2 ) = 5 ( 6 ) = 3 0